Transformasi Pembelajaran Jarak Jauh melalui Optimalisasi Media Pembelajaran Digital: Studi Empiris dan Implikasinya - Nurhopipah, Siti; Fauziyah, Nurul Hikmah; Ulfatulaelah, Eneng; Wicaksono, Dirgantara (YASIN, 2025)
Although the implementation of digital-based distance learning has been widely developed, comprehensive studies on the transformation of distance learning through the optimization of digital learning media in Indonesia remain relatively limited. This study aimed to examine the transformation of distance learning through the optimization of digital learning media based on recent empirical findings in Indonesia from 2021 to 2025. Using a descriptive qualitative approach with a comprehensive literature review, this study synthesised how the use of Learning Management Systems (LMS), video-based learning, mobile learning applications, interactive multimedia, and social media shapes the effectiveness of digital-based teaching. The findings showed that the integration of various digital platforms increased flexibility, accessibility, student engagement, and learning outcomes, particularly when supported by robust instructional design and educators’ digital competence, while social media functioned as supplementary learning support that facilitates real-time communication and collaboration. The implications include a shift in teachers’ roles towards facilitators and instructional designers, the need for competency-based curriculum redesign, and the strengthening of a more self-regulated learning culture. Theoretically, digital transformation in distance learning reinforces constructivist, connectivist, and multimodal learning perspectives. This study concludes that the optimization of digital media is a prerequisite for the development of an adaptive and future-oriented distance learning ecosystem, with recommendations to strengthen digital pedagogy training, enhance technological infrastructure, and establish sustainable digital learning policies to support long-term implementation.